GIANT TRICHOBEZOAR MIMICKING GASTRIC TUMOUR - Ali, Syed Asad; Soomro, Abdul Ghani; Jarwar, Muhammad; Memon, Abdul Sattar; Siddiqui, Akmal Jamal (Journal of Ayub Medical College Abbottabad, 2011)
Abstract: We present a case of giant gastric trichobezoar retrieved through a long gastrotomy in a 40 years old married women from rural Sindh with unreported psychological disturbance. Trichobezoar almost exclusively occur in females with an underlying psychiatric disorder. It has an insidious development of symptoms which accounts for its delayed presentation and large size at the time of diagnosis. They are associated with trichophagia (habit of compulsive hair eating) and are usually diagnosed on CT Scans or upper GI Endoscopy. They can give rise to complications like gastroduodenal ulceration, haemorrhage, perforation, peritonitis or obstruction with a high rate of mortality. The treatment is endoscopic, laparoscopic or surgical removal and usually followed by psychiatric opinion. Keywords: Trichobezoar, Psychiatric Disorder, Management